Banking Competition Measurement and Banking Sector Performance: Analysis of 4 ASEAN Countries - Buddi Wibowo (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
Many believe concentrated banking industry which is dominated by few big banks creates lower competition, high profitability, and low efficiency. The main issue in empirical testing of this hypothesis is how to measure banking competition level. Traditional measures of competition are concentration ratio and Herfindahl-Hirschman Index. This study uses three measures of banking level competition which are widely used in recent financial literature: Boone Indicator, Lerner Index and H-Panzar-Rosse statistics. Lerner Index and H-Panzar-Rosse statistics resulted a similar competition level conclusion, while Boone Indicator produced slightly different output. Industry concentration produced opposing results with those three level of industry competition measurement methods. The results show banking competition tend to be a monopolistic competition in ASEAN countries, especially in Indonesia which banks’ strategy basically were non-pricing strategy. Competition significantly caused lower profitability, while banking efficiency was not significantly affected by level of competition.DOI: 10.15408/sjie.v6i1.4547